Resveratrol Ameliorates Male Reproductive Dysfunction Induced By Pirimiphos-methyl In Rats (African Journal of Biomedical Research, 2023)
Exposure to Pirimiphos-methyl (POM) has been reported to adversely affect sperm functions, leading to male infertility. This study seeks to investigate the effect of resveratrol on POM induced male reproductive dysfunction. Twenty-four male Sprague-Dawley rats weighing between 165g – 200g were randomly divided into four groups of control, the POM group (received 62.5mg/kg POM/ b.w), POM + RES (received 62.5mg/kg POM and 20mg/kg body weight of resveratrol, and the RES group (received 20mg/kg body weight resveratrol) for 65 days. The results showed a significant decrease in body weight gain in the POM group, POM +RES group compared to the control. The relative liver weight of the POM group was also significantly increased compared with the control (p